Strategi Manajemen Pemasaran Syariah dalam Pengembangan Lembaga Pesantren: Studi Kasus di Pesantren Miftahul Ulum Lumajang - Husen, Muhammad (Published by the Postgraduate Program in Islamic Education Management, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, Indonesia, 2024)
This study examines sharia marketing management strategies in developing Islamic boarding schools through a case study at Pesantren Miftahul Ulum Lumajang. Using a qualitative case study approach, data were obtained from interviews, observations, and documentation. Findings show that the pesantren applies a holistic, value-based marketing strategy rooted in honesty, trustworthiness, and public benefit across the marketing mix. A hybrid model combines digital approaches with traditional pesantren networks, with the Kyai serving as an ethical guide, framing marketing as da'wah rather than mere economics. The study offers a conceptual model of Islamic marketing that is ethical, educational, and spiritually grounded, contributing to theory and providing practical insights for pesantren development. Penelitian ini mengkaji strategi manajemen pemasaran syariah dalam pengembangan pesantren melalui studi kasus di Pesantren Miftahul Ulum Lumajang. Dengan pendekatan kualitatif studi kasus, data diperoleh dari wawancara, observasi, dan dokumentasi. Hasil menunjukkan strategi pemasaran berbasis nilai kejujuran, amanah, dan maslahat pada seluruh bauran pemasaran. Model hybrid marketing diterapkan melalui kombinasi digital dan jaringan tradisional pesantren, dengan Kyai berperan sebagai penjaga etika sehingga pemasaran diposisikan sebagai dakwah. Penelitian ini menghasilkan model konseptual pemasaran syariah yang etis, edukatif, dan spiritual, serta memberi kontribusi teoritis dan praktis bagi pengembangan pesantren.